LABORATORY EVALUATION OF EFFICACY OF THREE DIATOMACEOUS EARTH FORMULATIONS AGAINST TRIBOLIUM CASTANEUM HERBST (COLEOPTERA: TENEBRIONIDAE) IN STORED WHEAT - Kabir, B. G. J. (European Scientific Journal, ESJ, 2013)
Laboratory experiments were conducted to evaluate three DE formulations - Protect-It, DiaFil 610 and Celite 209 at dose rates 500, 750 and 1000 mg/kg of wheat, against the red flour beetle Tribolium castaneum Herbst under ambient laboratory conditions (26 - 32°C and 48 - 65% r.h.). Mortality of exposed adults increased with increase in dose and exposure period; however consistency was notable only after 7days of exposure. With all DE formulations, mortality was low on grains treated at 500 and 750 mg/kg after 3 and 7 days of exposure. Protect-It was highly effectives at 1000 mg/kg causing 100% adult mortality after 3 days of exposure. Similarly, all the three DE formulations caused complete adult mortality on grains treated at 750 and 1000 mg/kg after 14 days of exposure. In addition, at these dose rates complete progeny suppression was recorded except on grain treated with DiaFil 610 at 750 mg/kg. The findings of this study have demonstrated that the efficacy of the three DE formulations to control T. castaneum and as potential alternative to synthetic insecticides.